IMF Committee on Balance of Payments Statistics : Annual Report 2014. (Balance of Payments Statistics; Balance of Payments Statistics ;, 2015)
The 2014 Annual Report of the IMF Committee on Balance of Payments Statistics (Committee) provides an overview of recent trends and discrepancies in global balance of payments statistics, and summarizes the Committee's work program during 2014 and the issues the Committee plans to address in the coming year.